Digital literacy analysis: A case study of Telkom Indonesia in exploring its work environment dynamics - Pertiwi, Intan Suci Kasih; Lestari, Martha Tri (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
Digital literacy is increasingly recognised as a crucial skill in today's work environment, particularly in the context of rapidly advancing technology. This study aims to analyse the level of digital literacy among employees at PT Telkom Indonesia Graha Merah Putih Bandung and its impact on work productivity. Qualitative research methodology was employed with employees of the company serving as the research population. Both primary and secondary data were utilised, gathered through interviews, observation, and documentation. This study used three types of informants with each being represented by one employee. The findings reveal that digital literacy, encompassing proficiency in utilising digital communication tools and platforms, significantly influences the work productivity of PT Telkom Indonesia employees. Moreover, the development of digital literacy has identified that it is playing pivotal role. The study underscores the importance of digital transformation initiatives and enhancing employee digital literacy to drive improvements in work productivity.